Il CIRSE e la tradizione degli studi storico-educativi in Italia. Tendenze storiografiche tra presente e futuro - Dorena Caroli (Studi sulla Formazione)
This article aims at presenting the origins and the evolution of the disciplinary field of history of pedagogy in Italy. It is a process to which the Centro Italiano per la Ricerca Storico-Educativa (CIRSE), founded in 1980, contributed and which continues to this day. After an introduction describing the scientific changes occurred in the two decades preceding the foundation of CIRSE – similar in some ways to what happened in France – this paper consists of four parts describing the definition process of the study of history of pedagogy initiated in the cultural context of the 1968 revolution; the methodological and epistemological renewal established on the basis of the scientific activities carried out by CIRSE; the different legislation steps that led to the development of an independent field history of pedagogy at university level; finally, the current potential of CIRSE in the promotion of networks and scientific collaboration among Italian universities.